2021
DOI: 10.3390/neurosci2010006
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines in Pediatric Pilocytic Astrocytomas: A Clinico-Pathological Study

Abstract: Pilocytic astrocytomas (PCA) are WHO Grade I tumors with a favorable prognosis. Surgical resection is usually curative. Nonetheless, progressive and/or metastatic disease occurs in 20% of patients. For these patients, treatment options are limited. The role of the immune system in PCA has not previously been reported. We hypothesize that the circulating cytokines contribute to tumorigenicity in PCA. This is an exploratory study with a focus on the identification of circulating cerebrospinal (CSF) cytokines ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…The study found that patients with ALL exhibit higher levels of a group of correlated cytokines, including IL-1β, IL-8, TNF-α, and VEGF, at birth compared to their healthy counterparts [ 92 ]. Similar cytokine profiling has been conducted in children with B-ALL, anaplastic lymphoma kinase-positive anaplastic large cell lymphoma, pediatric pilocytic astrocytomas, as well as children with cancer and febrile neutropenia [ 93 , 94 , 95 , 96 ]. These findings collectively suggest an intriguing association between cytokine levels and tumor development.…”
Section: Influence Of the Immune Microenvironment On Pediatric Tumor ...mentioning
confidence: 99%
“…The study found that patients with ALL exhibit higher levels of a group of correlated cytokines, including IL-1β, IL-8, TNF-α, and VEGF, at birth compared to their healthy counterparts [ 92 ]. Similar cytokine profiling has been conducted in children with B-ALL, anaplastic lymphoma kinase-positive anaplastic large cell lymphoma, pediatric pilocytic astrocytomas, as well as children with cancer and febrile neutropenia [ 93 , 94 , 95 , 96 ]. These findings collectively suggest an intriguing association between cytokine levels and tumor development.…”
Section: Influence Of the Immune Microenvironment On Pediatric Tumor ...mentioning
confidence: 99%